2013
DOI: 10.1111/coa.12118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of oral function in acute and recovery phase of idiopathic facial palsy; a preliminary controlled study

Abstract: Oral functions were decreased by peripheral facial palsy. Oral vestibular cleansing capability was more significantly associated than masticatory efficiency with facial muscle function. Our data suggest that peripheral facial palsy impairs eating and worsens oral hygiene, which may result in oral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…After 6 months, it becomes more evident as to which patients will have moderate to severe sequelae (5) . PFP may result in physical, psychological, social, aesthetic, and functional disorders, once it adversely affects facial expressions (nonverbal communication) and may cause changes in the orofacial functions (7) . Studies indicate that patients with axonal loss may more often present sequelae and functional adaptations (8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…After 6 months, it becomes more evident as to which patients will have moderate to severe sequelae (5) . PFP may result in physical, psychological, social, aesthetic, and functional disorders, once it adversely affects facial expressions (nonverbal communication) and may cause changes in the orofacial functions (7) . Studies indicate that patients with axonal loss may more often present sequelae and functional adaptations (8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that the poorer health of patients with FP is the result of the lack of targeted muscle movements involved in natural cleaning mechanisms of the oral cavity. A study [ 6 ] on 14 patients with acute idiopathic FP reported that the ability to clean the vestibule was significantly lower compared to healthy controls and on their PS compared to their NPS (p ≤ 0.001). Another study confirmed these findings [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 6 ], including a quantitative evaluation of oral function in the acute and recovery phase of idiopathic facial palsy, has provided an initial indication that peripheral facial paralysis impairs oral hygiene and can promote oral disease. However, even after reinnervation, the coordination of the lips and the corner of the mouth is a long-term problem for most patients.…”
Section: Introductionmentioning
confidence: 99%
“…Os pacientes acometidos por esse problema tendem a desenvolver distúrbios físicos, pela má alimentação, psicológicos, pelo auto isolamento decorrente do constrangimento da doença e estéticos funcionais, pela doença prejudicar a realização das expressões faciais dificultando as relações sociais. Com isso, tornando-se de extrema importância o seu tratamento para a melhora da qualidade de vida dos enfermos (KATO Y, et al, 2013;WENCESLAU LGC, et al, 2016).…”
Section: Introductionunclassified